IMPLEMENTASI SISTEM INFORMASI AKADEMIK BERBASIS CLOUD UNTUK MENINGKATKAN EFISIENSI ADMINISTRASI AKADEMIK - Setyorini, Setyorini (JATISI, 2025)
The advancement of information technology has brought many benefits to the world of education today, creating school websites and developing computerized educational information systems are some of the applications of information technology. Course data processing that is usually done by schools is still done manually, and the data collection system still uses paper and notes, so it is easy to cause loss and damage to existing data. The development of the system solves the problems of educational data processing by creating a cloud computing academic information system that provides information such as student information, teacher list, subjects, student results, student learning results, and student participation announcements via SMS to parents. The programming languages used to build this information system are PHP and MySQL databases. Therefore, the existence of this system can contribute to accelerating the process of academic data processing. Moreover, with a cloud computing platform, data information can be viewed in real-time. Based on the results of tests conducted on the system from a functional point of view, it can be concluded from the table that up to 10 sample data provide the correct values according to the following calculations: precision values 10/10 * 100 = 100 %. These results show that the school information system is running well and as expected.